Indigenous conflict management practices in Ethiopia: a systematic literature review - Robson Mekonnin Shiferaw; Kenenisa Lemi Debela (Cogent Business & Management, 2024)
This research aims to examine recent writing on the dynamics of indigenous conflict management practices in Ethiopia to review the concept and create a more thorough theoretical description from a conceptual perspective. The study demonstrates that there are scattered studies across countries about the conceptual application of dynamics of indigenous conflict management practices in Ethiopia within the scope of the review (2001 to 2022). Because of this, whether the firm is large or little, for profit or not, a thorough understanding of the dynamics of indigenous conflict management practices in Ethiopia is essential for all levels of modern organizations as an alternative option. To help practitioners build and implement dynamics of indigenous conflict management practices in pastoralist and agricultural ways of economic lifestyle comparatively with statutory law. Analyzing the current state of research and management orientations in this field will be useful to the scientific community and society at large. Many methodological (exclusive search) constraints exist in this review, which may limit how well it can be used with additional case studies. The dynamics of indigenous conflict management practices in Ethiopia are essential parts of conflict resolution relevant to formal conflict resolution mechanisms in most of the pastoral communities in Ethiopia. It is the first of its type to use a systematic review analysis of the dynamics of indigenous conflict management practices in Ethiopia to demonstrate how the concepts relate to managing conflict conventional by carefully reviewing a large body of research in this field. Both ideas have not been investigated or addressed before. A full understanding of the current state of indigenous conflict management research conceptualization needs the attention of policy crafters for those communities that developed the system through generational paths for centuries in Ethiopia before formal conflict resolution or modern ways of solving conflict.
Keywords: 650; Dynamics; Indigenous; Conflict management; practices; Ethiopia